The tale of Beowulf : a digital edition - Jones, D (University of Oxford, 2019)
This data set consists of 12 image files in TIFF format, and an XML file. These files were created as part of a Digital Editions course, run by the Taylor Institution Library, during Michaelmas Term 2019. The course required participants to create a digitised version of a printed text. This text is pages 26-37 from Morris, William, and A. J. Wyatt, 'The Tale of Beowulf', 1895 (St Anne's College Library 821.13 11 / Taylor Institution Library ARCH.FOL.E.1895). The images of the original text were created using a digital camera and then converted to TIFF format using Corel PaintShop Pro 2019. The XML file included here contains an encoded transcription of the original text, created and edited using Oxygen XML Editor, according to Text Encoding Initiative (TEI) guidelines.